Pola Tutupan, Penggunaan, Serta Tantangan Kebijakan Perlindungan Ekosistem Gambut di Kabupaten Bengkalis - Sandhi Imam Maulana; Lailan Syaufina; Lilik Budi Prasetyo; Muhammad Nur Aidi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Since the issuance of Government Rule No. 71/2014 jo. No. 57/2016, there has been a wide debate, because those rules may trigger other problems such as food security, social, economic, political, as well as peatland cultivation security. Considering this issue, this study aims to analyze challenges in implementing peat protection policies as textually arranged in Government Rule No. 71/2014 jo. No. 57/2016, in Bengkalis Regency. Overall, in order to discuss both of rule in form and rule in use aspects, this study was conducted using maps overlay technique and content analysis on Government Rule No. 71/2014 jo. No. 57/2016. Based on those approaches, this study shows that there are four challanges in implementing previously mentioned peat ecosystem protectetion policies in Bengkalis Regency, particularly in regard to the measurement of damaged peatland criteria, frictions between protection incentives and pressure on peatland conversion, significant economic contraction, up to the emergence of new open access areas that often be illegally occupied and worsening peatland existing conditions. This finding implies that the government as the regulator in the implementation of peat ecosystem protection policies should open a wider room for policy improvements, in order provide a more balanced consideration to three important aspects of sustainable development, which is not only limited to environmental sustainability, but also covering both of social and economic sustainability.